PENGEMBANGAN KERAJINAN MAINAN ANAK DESA JIKEN, TULANAGAN, SIDOARJO DALAM MENINGKATKAN KAPASITAS PRODUKSI - Suprayitno, Eko Agus; Hindarto, -; Evianti, Ade (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
Jiken village located in the district Reinforcement, Sidoarjo regency, ± 10 km from downtown Sidoarjo. Jiken village is a village of SMEs engaged in the activities of Household Appliance Craftsmen, Artisans Batik, Embroidery Craftsmen, Artisans Bags and Aquaculture in ponds. The rest of the villagers Jiken many craftsmen who work as children's toys. In this dedication program raised issues 2 Partners, which Partner 1 and Partner 2, both the partners work as artisans craft toys. Crafts Toys effort is capable of producing 48 scores for 2 weeks, scores of 3.4 per day. Development of a toy Kids Crafts Village Jiken Tulanagan Kab. Sidoarjo in increasing production capacity through science and technology program for Community (IbM) Partner 1 and Partner 2 is going well and according to plan. Several problems Partner 1 (Artisans Children toys) and Partner 2 (Craftsmen toys Children) has been given a solution according to plan and the process runs smoothly solutions which include among others: 1). Assist the process of production, particularly in providing assistance Making cans cutting tools, to be able to do the cutting fast and qualified cans (canned chunks results have pieces of the same pattern). As well as providing aid Pengeplong zinc/tin to increase the production capacity of zinc perforation ready assembled into a tool toys are ready for use. Then conduct training on cutting tools and pengeplong pengoprasian zinc/tin. Results of this aid shown to increase the production capacity of up to 3-fold. Namely the production capacity of 1920 products every 28 days, increasing to 5760 products every 28 days. 2). Provide training on procedures for preparing the financial statements properly and according to the rules - the rules so that banks can use to access funding from banks and analyzes the development of the business. 3). Assist in obtaining a license for the product brand logo to enhance the competitiveness of products and the level of consumer confidence in the product. Logo and realize products that are legal in toys Child Craft Tool Partner 1 and Partner 2. Logo that carried the "Bintang Tiga Jaya"